Perlindungan Hukum Terhadap Pihak yang Mengalami Pemberhentian Kerjasama Secara Sepihak Terkait Pengelolaan Lahan Parkir Berdasarkan Perbuatan Melawan Hukum - Kurniawan, Fredy Bagus (UM Purwokerto Press, 2024)
This research discusses the legal protection of the injured party due to the unilateral termination of the cooperation agreement, with a case study between PT Kitita Alami Propertindo and PT Alpha Servis Indonesia. The unilateral termination of the agreement by PT Kitita Alami Propertindo without regard to the agreed agreement caused losses to PT Alpha Servis Indonesia, which then filed a lawsuit. This research uses a normative juridical method with a case approach to identify and analyze the elements of tort according to Article 1365 of the Civil Code. The results showed that the actions of PT Kitita Alami Propertindo fulfilled the elements of a tort, including fault, loss, and causal relationship. This research concludes that legal protection for the injured party must be enforced through a fair legal process, as well as the importance of implementing agreements in good faith to prevent future disputes.